Analysis of Vocational High School Teachers’ Competency Profiles - Yatwawan Lolo; Putu Sudira (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Educators serving in Vocational High Schools have not met the competency standards. This study aimed to describe: (1) pedagogy, professional, personality, and social competence of teachers in vocational high schools, and (2) the performance of teachers in vocational high schools. This descriptive study was conducted at four vocational high schools in North Morowali that have been nationally accredited. The respondents consisted of 23 principals, vice principals, heads of the study program, and 178 student. The data were collected using documentation and questionnaire.  It were further analyzed using descriptive analysis. The results showed that:  (1) 66.76% of the teachers have the competence of the teacher's pedagogy with high category, 77.92% of the teachers have the professional competence with high category; 78.66% of the teachers have the personality competence with high category; 79.82% of the teachers have social competence with high category, (2) 75.35% of the teachers have the performance with high category.